Closure of Large Meningomyelocele Wound Defects with Subcutaneous Based Pedicle Flap with Bilateral V-Y Advancement: Our Experience and Review of Literature - Kesan, Krushnakumar; Kothari, Paras; Gupta, Rahul; Gupta, Abhaya; Karkera, Parag; Ranjan, Ritesh; Mutkhedkar, Kedar; Sandlas, Gurusev (European Journal of Pediatric Surgery, 2015)
Background Meningomyelocele is a defect of the spinal cord, vertebrae, and the overlying skin and is the most common form of open spinal dysraphism. Rapid closure of the back defect in the early postnatal period is mandatory to reduce the frequency of infection-related complications of the central nervous system. Majority of the cases present with small defects, which can be closed primarily, with or without subcutaneous dissection. However, direct closure is not possible in 25% of the cases. Different types of local flaps (skin or muscle flaps) are widely used for covering the skin defects; and with varying results.Patients and Methods A prospective nonrandomized study was conducted in the department of pediatric surgery at a tertiary hospital, from September 2007 to October 2011. Overall 35 patients with large meningomyelocele defects that could not be closed primarily were included in the study. All patients were treated using subcutaneous tissue based pedicle flap with bilateral V-Y advancement.Results There were 27 neonates, 7 infants, and 1 child, with a male:female ratio of 1.19:1. There were 3 thoracolumbar, 14 lumbar, 14 lumbosacral, 3 sacral, and 1 multiple meningomyelocele defects with an average size of 8.5 cm (range 6.5–11 cm). Average intraoperative blood loss was 8 mL (range 6–10.5 mL). Average operative time which included flap reconstruction time, after closure of dura, was 38.6 min. Total seven patients had wound complications viz. fat necrosis (n = 2), flap necrosis (n = 2), hematoma (n = 1), cerebrospinal fluid leak followed by wound dehiscence (n = 1), wound infection which led to meningitis (n = 1). Average healing time for flap repair was 7.52 days. Overall 80% (n = 28) of the patients had good flap texture and contour with satisfactory cosmesis.Conclusion Closure of large meningomyelocele wound defects with subcutaneous based pedicle flap with bilateral V-Y advancement is an effective technique. The main advantages of this technique are its simplicity, short operative time, good tolerance, early healing, and good cosmetic outcome with an excellent flap texture and contour match with minimal complications.
Keywords: meningomyelocele; subcutaneous based pedicle flap; bilateral V-Y advancement